Profiling Ethiopian finger millet (Eleusine coracana) accessions for major agronomic traits and nutrient composition under varying drought stress - Gebreyohannes, Adane; Hussein, Shimelis; Mashilo, Jacob; Odeny, Damaris A.; Taye Mindaye; Ojulong, Henry; Ojiewo, Chris O. (Springer, 2025)
Finger millet (Eleusine coracana L. Gaertn) is a drought-resilient cereal with notable agronomic and nutritional value, yet remains underutilized due to limited research and product development. The objective of this study was to profile genetically diverse Ethiopian finger millet accessions for major agronomic traits, drought response, and nutritional compositions under contrasting drought stress conditions to select genotypes for breeding or production. This study evaluated 448 Ethiopian accessions (landraces and improved varieties) for agronomic performance, drought responses and nutrient composition across three moisture regimes: non-stressed (Arsinegelle: AN), moderately drought-prone (Maitsebri: SH), and severely drought-stressed (Meiso: MI). Field trials employed a row-column design (64 × 7 with two replications). Significant (P < 0.001) effects of genotype, environment, and genotype × environment interaction were detected for all traits. Grain yield (GY) declined by ~ 60% at MI site. The test genotypes varied considerably at MI for key traits: days to 50% flowering (DF) (78.5–107.5 days), days to maturity (DM) (101.0–149.5 days), grain yield (GY) (0.5–3.2 t/ha), grain iron (53.6–81.0 ppm) and grain zinc (67.8–83.1 ppm) suggesting conisderable genetic varaition for selection. Black‐seeded genotypes maintained higher GY and Fe/Zn under drought, while red‐seeded types flowered and matured earlier and produced larger seed size. Broad‐sense heritability exceeded 60% for drought tolerance (Drt) score, DF, and DM, but remained below 30% for plant height, starch content and GY. GY was negatively correlated with DF, DM, Drt and stay-green traits, but positively correlated with seed weight across environments. Principal component analysis explained > 67% of the variance in key traits across test sites, and hierarchical clustering grouped genotypes into four clusters. Eight accessions (G141, G423, G297, G247, G171, G204, G294, and G46) were identified as promising candidates for direct use or breeding for improved yield, nutrient density and drought resilience.